Developmental origins of disease highlight the immediate need for expanded access to comprehensive prenatal care - Chloe R. McDonald; Andrea M. Weckman; Julie K. Wright; Julie K. Wright; Andrea L. Conroy; Kevin C. Kain; Kevin C. Kain; Kevin C. Kain; Kevin C. Kain (Frontiers Media S.A., 2022)
The prenatal environment plays a critical role in shaping fetal development and ultimately the long-term health of the child. Here, we present data linking prenatal health, via maternal nutrition, comorbidities in pregnancy (e.g., diabetes, hypertension), and infectious and inflammatory exposures, to lifelong health through the developmental origins of disease framework. It is well-established that poor maternal health puts a child at risk for adverse outcomes in the first 1,000 days of life, yet the full health impact of the in utero environment is not confined to this narrow window. The developmental origins of disease framework identifies cognitive, neuropsychiatric, metabolic and cardiovascular disorders, and chronic diseases in childhood and adulthood that have their genesis in prenatal life. This perspective highlights the enormous public health implications for millions of pregnancies where maternal care, and therefore maternal health and fetal health, is lacking. Despite near universal agreement that access to antenatal care is a priority to protect the health of women and children in the first 1,000 days of life, insufficient progress has been achieved. Instead, in some regions there has been a political shift toward deprioritizing maternal health, which will further negatively impact the health and safety of pregnant people and their children across the lifespan. In this article we argue that the lifelong health impact attributed to the perinatal environment justifies policies aimed at improving access to comprehensive antenatal care globally.